IR heterodyne spectrometer MILAHI for continuous monitoring observatory of Martian and Venusian atmospheres at Mt. Haleakalā, Hawaii. (July 2016) - Nakagawa, Hiromu; Aoki, Shohei; Sagawa, Hideo; Kasaba, Yasumasa; Murata, Isao; Sonnabend, Guido; Sornig, Manuela; Okano, Shoichi; Kuhn, Jeffrey R.; Ritter, Joseph M.; Kagitani, Masato; Sakanoi, Takeshi; et al.
Abstract: A new Mid-Infrared Laser Heterodyne Instrument (MILAHI) with >10 6 resolving power at 7–12 μm was developed for continuous monitoring of planetary atmospheres by using dedicated ground-based telescopes for planetary science at Mt. Haleakalā, Hawaii. Room-temperature-type quantum cascade lasers (QCLs) that cover wavelength ranges of 7.69–7.73, 9.54–9.59, and 10.28–10.33 μm have been newly installed as local oscillators to allow observation of CO2, CH4, H2 O2, H2 O, and HDO. Modeling and predictions by radiative transfer code gave the following scientific capabilities and measurement sensitivities of the MILAHI. (1) Temperature profiles are achieved at altitudes of 65–90 km on Venus, and the ground surface to 30 km on Mars. (2) New wind profiles are provided at altitudes of 75–90 km on Venus, and 5–25 km on Mars. (3) Direct measurements of the mesospheric wind and temperature are obtained from the Doppler-shifted emission line at altitudes of 110 km on Venus and 75 km on Mars. (4) Detections of trace gases and isotopic ratios are performed without any ambiguity of the reproducing the terrestrial atmospheric absorptions in the observed wavelength range. A HDO measurement of twice the Vienna Standard Mean Ocean Water (VSMOW) can be obtained by 15-min integration, while H2 O of 75 ppm is provided by 3.62-h integration. The detectability of the 100 ppb-CH4 on Mars corresponds to an integration time of 32 h. Highlights: IR laser heterodyne instrument was newly developed for planetary atmospheres. New wind and temperature retrievals on Mars and Venus were investigated. QCLs were applied to allow observation of CO2, CH4, H2 O, H2 O2 and their isotopes.